Memory consolidation - Sakakibara, Manabu, 1949-; Ito, Etsuro (Neuroscience research progress series., 2015)
Learning and memory are necessary, fundamental functions that animals need in order to survive and adapt to any environment. The ability to learn and form memory depends on changes occurring in neuronal circuits. These changes occur at both the synaptic level and at the level of changes in intrinsic membrane properties of neurons. Such changes involve physical, structural changes (including growth of new processes as well as retractions of other processes.) Some of these changes may persist throughout the life of the organism while others last for relatively short times. While learning and mem.